TAHLILAN SEBAGAI SINKRONISASI AGAMA DAN BUDAYA: (Perspektif Legal Maxim) - Firda Annisa (Sahaja: Journal Sharia and Humanities, 2022)
Before Islam came, the majority of Indonesian people at that time are still Hinduism. Then Walisongo came to bring Islam and started to spread Islam doctrines in order to call the Indonesian who at that time were still keep up with Hindu doctrines, one of their doctrine called "pinde pitre yajna" which is better known as "tahlilan" right now. The pinde pitre yajna doctrines originally had a ritual/activity called "jagongan" this ritual works by talking late into the night, gambling, drinking liquor and also reciting magic spells at the funeral home. The method of discours that used by Walisongo is the method of assimilation of Islamic - Hindu culture by changing these bad habits with activities that are more Islamic. The magic spell that is usually recited is changed to the t}ayyibah (good) sentences. However, there are several Islamic sects that contradict with this method and then state that the teachings conveyed through the Walisongo contain elements of bid’ah (acts that were not taught by the Prophet Muhammad). This paper uses a qualitative method in terms of literature. In this journal the author wants to explain the facts of the concept of tahlilan using the maxim law perspective (ka>idah fiqhiyyah), namely the 'urf (tradition). Tahlilan can be justified as 'urf which is not in Islam because tahlilan is a misleading tradition then guided by the Walisongo in accordance with Islamic law without any coercion.